A new indicator of elastic spectral shape for the reliable selection of ground motion records. - Mousavi, Mehdi (Earthquake engineering & structural dynamics.)
How to select a limited number of ground motion records (GMRs) is an important challenge for the non-linear analysis of structures. Since epsilon (Esa) is an indicator of spectral shape, which has a significant correlation with the non-linear response of a structure, the selection of GMRs based on the hazard-related target Esa is a reasonable approach. In this paper, an alternative indicator of spectral shape is proposed, which results in a more reliable prediction of the non-linear response for the structures with the natural period of 0.25 to 3.0 s. This new parameter, named eta (n), is a linear combination of Esa and the peak ground velocity epsilon (Epgv). It is shown that n, as a non-linear response predictor, is remarkably more efficient than the well-known and convenient parameter ESa. The influence of n-filtration in the collapse analysis of an eight-story reinforced concrete structure with special moment-resisting frames was studied. Statistical analysis of the results confirmed that the difference between e-filtration and n-filtration can be very significant at some hazard levels. In the case of this structure, the resulting annual frequency of collapse was found to be lower in the case of n-based record selection, in comparison with the E-based record-selection approach.